Pengaruh Faktor Makroekonomi dan Faktor Spesifik Bank terhadap NPF Bank Umum Syariah di Indonesia - Ayu Sri Wahyuni; Fatmi Hadiani; Banter Laksana; Benny Barnas (Journal of Applied Islamic Economics and Finance, 2023)
This study aims to determine the macroeconomic factors and specific bank factors that influence Non-Performing Financing (NPF) of Sharia Commercial Banks (BUS) in Indonesia from 2015 to 2020 annually. Data analysis method used in this study is panel data regression with 9th version EViews by taking a sample of 10 Sharia Commercial Banks (BUS) in Indonesia, the variable of inflation has a positive significant effect, the variable of GDP has a negative significan, and BI Rate has no significant effect. Meanwhile, the specific bank factors variable of FDR has a positive and significant effect toward NPF of Sharia Commercial Banks (BUS) in Indonesia. Lastly, the variable of ROA and CAR have no effect toward NPF of Sharia Commercial Banks (BUS) in Indonesia.